Strategi Komunikasi Gerakan Bersihkan Indonesia dalam Membangun Agenda Publik - Rahayu, Dona; Prabhawa, M Dikky; Susi, Susi (Translitera : Jurnal Kajian Komunikasi dan Studi Media, 2022)
Air pollution causes public health problems, especially in vulnerable communities. Air pollution is also a contributor to climate change in Indonesia. To reduce air pollution and the rate of climate change, a group of civil society organizations that are members of Clean Indonesia seeks to build a public plan by using a communication strategy to influence the policies issued by the government to abandon fossil energy as the main cause of air pollution. This research is qualitative by using interviews and in-depth observations of Clean Indonesia. It is concluded that the communication strategy carried out by Bersih Indonesia to build a public agenda uses media advocacy by utilizing interpersonal and mass communication channels. The aim is to optimize persuasion and open up public space for the community. The news regarding the refusal of foreign bank financing to fund fossil energy projects indicates that the expected effect is achieved in public agenda communication. Still, the absence of regulations or policies issued by the government to reduce the use of fossil energy indicates that the effect of public agenda communication to the government has not been achieved.